PENERAPAN AKUNTANSI PERTANGGUNGJAWABAN SEBAGAI ALAT PENILAIAN KINERJA MANAJEMEN KURIR DAN LOGISTIK - Rastina (Funds: Jurnal Ilmiah Akuntansi, Keuangan, dan Bisnis, 2024)
The Parepare Branch Office of PT. Pos Indonesia has achievement targets that need to be met. However, in practice, it frequently falls short of these established targets.. By implementing responsibility accounting in the company, the management performance will be better. Meanwhile, good management performance will make it easier for companies to implement responsibility accounting so that company goals can be achieved. This research aims to find out how 1) Procedures for implementing operational activities at PT. Pos Indonesia (Persero) Parepare Branch Office, 2) implementation of responsibility accounting based on responsibility accounting requirements at PT. Pos Indonesia (Persero) Parepare Branch Office, 3) the role of responsibility accounting in assessing management performance at PT. Pos Indonesia (Persero) Parepare Branch Office. This research method uses a qualitative case study approach with a type of field research, and the data collection methods in this research are observation, interviews and documentation. The data analysis techniques include data collection, data reduction and data presentation. The research results show that: 1) Procedures for implementing operational activities at PT. Pos Indonesia (Persero) Parepare Branch Office corporate services include offers and Cooperation Agreements with corporate partners, receipt of Goods/Documents, sorting and packing processes, up to delivery to the Destination, followed by tracking and Monitoring, and finally the issuance of Billing Letters/Payment Invoices. 2) PT. Pos Indonesia (Persero) Parepare Branch Office has implemented responsibility accounting in accordance with the conditions for its implementation, namely there is an organizational structure in the company, preparation of a budget, separation of controlled and uncontrolled costs, classification of account codes, and there is accountability reporting. 3) By using responsibility accounting as a performance assessment tool, the accountability of managers and employees becomes clearer, and can increase their motivation to work better because their performance will be evaluated and rewarded fairly.